The Evidence for Perfect y‛aqtul and Jussive yaqt‛ul in Proto-Semitic - Hetzron, R.
3-5: Akkadian; the minimal pair liprus (< *lū+iprús) and lū iprus indicates different stresspatterns for proto-Akkadian jussive and perfect (preterite).